Determinan tax avoidance pada perusahaan pertambangan di Indonesia - Hapsari, Dini Wahjoe; Agustya, Fanisa Putri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study means to analyze the impact of deals development, fixed resource force and influence on charge evasion. Charge evasion is a citizen's work to legitimately stay away from charges and be protected in light of the fact that it doesn't go against the arrangements and regulations. The populace in this study are mining area organizations recorded on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The exploration test is purposive inspecting, so a sum of 18 organizations. The consequences of this study demonstrate that deals development, fixed resource force and influence all the while affect charge aversion. While to some degree deals development and fixed resource power emphatically affect charge aversion, yet influence meaningfully affects charge evasion. As a result, if a company's sales increase, its profitability also rises, and its performance improves. The higher the sales profit, the more the company's profitability rises, which also supports the annual increase in sales growth.